Developing a Framework Linking Organizational Creativity Climate, Knowledge Acquisition, and R&D Performance - Ling Tan, Cheng; Mohd Nasurdin, Aizzat; Fern Yeo, Sook (International Journal of Engineering and Technology, 2018)
R&D is the key for the knowledge-intensive and high value-added innovations in the firms. To expedite R&D activities, the Malaysian government increased its R&D expenditure to motivate R&D engineers to innovate, to engage actively in the commercialization of patents and the filing of intellectual property. This study aims to identify environmental factors that can intensify the R&D performance and increase the potential for innovations to be commercialized. Extensive literature review indicated that organizational creative climate influences R&D performance. Hence, organizational creative climate has been proposed as a significant predictor of R&D performance. However, inconsistent findings have been reported by various researchers. Therefore, knowledge acquisition capability is added as an intervening variable that can influence the relationship between organizational creative climate and R&D performance. To the researcherâ€™s knowledge, no attempt has been made to integrate the organizational creative climate with knowledge acquisition and R&D performance. It is hoped that this study will result in a better understanding of the factors that can influence R&D performance, particularly among medical devices manufacturers.Â